Tadeusz Kubiak i Anna Kamieńska: poetyckie spotkania z bratem Albertem - Kozaczewski, Jakub (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The core of the article is the comparative analysis and interpretation of two poems dedicated to St. Brother Albert: „Brother Albert’s Monastery” by Tadeusz Kubiak and „Meeting with Brother Albert” by Anna Kamieńska. Author’s thesis leads to the conclusion that Brother Albert as a person is not autonomous theme in Kamieńska and Kubiak work - on a different level of understanding poets treat Brother Albert’s figure more like a pretext to unveil their own reflections and artistic thoughts.